A Mobile Health Breast Cancer Educational and Screening Intervention Tailored for Low-Income, Uninsured Latina Immigrants - Maria De Jesus; Shalini Ramachandra; Alexis De Silva; Shirley Liu; Ethan Dubnansky; Kingsley Iyawe; Astrid Jimenez; Laura Logie; M.C. Jackson (Mary Ann Liebert, 2021)
Objective: To investigate the efficacy of mobile health (mHealth) intervention strategies that delivered either personalized, culturally, and linguistically tailored cell phone voice messages or text messages related to breast cancer and prevention, compared to the control group, to determine which strategy is more likely to increase breast cancer knowledge and screening mammography among low-income Latina immigrants. Methods: This randomized controlled trial assigned 256 Latina immigrants 40 years of age or older to one of three groups: an automated cell phone voice message group, an automated text message group, or the control group (mail). The mHealth intervention employed a comprehensive approach that included breast cancer and prevention education and free mammography screening. Outcome measures included knowledge of breast cancer and breast cancer prevention, and adherence to screening mammography. Results: There was a general increase in breast cancer knowledge after the educational intervention for all the groups [p?=?0.01, t(199)?=?3.996]. Knowledge increase and mammography adherence did not differ based on group. Conclusion: More important than the actual method of communication is how breast cancer and prevention messages are constructed, who the messenger is, and the enabling factors that facilitate screening adherence. A breast cancer preventive intervention program that is personalized, culturally and linguistically tailored, and offers a free or low-cost mammogram holds promise to be an effective method in reaching an underserved Latina population with a high breast cancer burden.